Wen-hui Tsai, Patterns of Political Elite Mobility in Modern China, 1912-1949, Taiwán, Chinese Materials Center, 1983, pp. 274 (Asian Library Series, núm. 34). - Connelly, Marisela (Estudios de Asia y África, 1986)
-